The Role of Mangroves In Mitigation of Ecosystem Degradation Threats In Gunung Anyar city of Surabaya - Ni Dewi Ambal Ikka (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2023)
The coast of Surabaya City is dominated by mangrove forest ecosystems. The mangrove forest experiences a lot of shrinkage every year. The shrinkage that occurs in mangrove forests is not only caused by natural factors (abrasion and wind) but also due to logging activities by local communities. The degradation that occurs in mangrove forests is largely influenced by waves and tides. The existence of mangrove forests is thought to be very important for reducing the threat of degradation and can play a role in mitigating damage to existing ecosystems. The function of mangrove forests in mitigating the threat of degradation has encouraged a deeper study of mangrove forests which are thought to have a physical function as a barrier to ecosystem damage. The method used is a survey method with sampling using a transect line technique. The data collection technique in the field uses a transect line technique whose placement has been designed. The research results showed that three types were found, namely Avicennia marina, Rhizophora Apiculata, Ceriops candra. The tree level is calculated by the cover and density values ​​(trees/ha) to determine the standard criteria for determining mangrove forest damage. The cover level is very high with a final value of 99.61%. The results of the calculation of the density value (trees/ha) are above>150. amounting to 14,866.67, this shows that the density of trees in the Gunung Anyar mangrove forest is very high. Based on data from analysis of the Gunung Anyar mangrove forest, in general it has the ability to minimize degradation.